A Reexamination of Source Monitoring Deficits in the Elderly: Evidence for Independent Age Deficits of Item and Source Memory - Jeremy Tree (Brain Impairment, 2004)
Within the experimental literature there is substantial evidence of larger age-related deficits in retrieving source information relative to item-based information. However, this evidence is potentially subject to methodological criticism given that several studies have argued for the presence of source-monitoring deficits by examining source memory contingent on correct recall of item information but not the reverse. In order to address this potential shortcoming our study examines recall of both item information contingent on correct source judgement and source-based information contingent on correct recall of item information. We demonstrate that when this novel type of analysis is conducted, there are age deficits for both source and item information, and no evidence of a selectively greater source-monitoring deficit in the elderly. The results are discussed with reference to two overarching theoretical positions concerning age-related deficits in memory performance.